Wheelchairs with Portable Ramps (Waffle) Help the Daily Mobilty of Students with Disabilities - Emay Mastiani; Reza Febri Abadi; Siti Nur; Eka Yuli Astuti; Khairil Fikri (Edumaspul: Jurnal Pendidikan, 2024)
Students with physical disabilities often face various complex and diverse challenges in living their campus life. These challenges are not only limited to academic aspects, but also cover various aspects of daily life, including social interaction, access to campus facilities, and participation in various extracurricular activities. One of the most crucial aspects and often a major obstacle is the issue of mobility. Mobility is a very important basic need, but for students with physical disabilities, moving from one place to another on campus is often a very big challenge. Many buildings and facilities on campus are not designed with accessibility needs for people with disabilities in mind, so they have to struggle harder to be able to move around, attend classes, or simply participate in campus activities. This is where the important role of the Wheelchair with Portable Ramp (WAFEL) comes in, an innovation specifically designed to help overcome this mobility problem. WAFEL offers a very practical and effective solution, allowing students with physical disabilities to move more freely and independently in carrying out daily activities on campus. With WAFEL, students with physical disabilities are not only helped in terms of mobility but also have greater opportunities to participate fully in campus life, which can ultimately improve their quality of life and academic achievement